Akuntabilitas Manejerial Kepala Sekolah dalam meningkatkan Motivasi berprestasi Guru di Sekolah Dasar Islam Terpadu - Kadarsih, Sri; Latif, Mukhtar; Wahyudi, Wahyudi (MODELING: Jurnal Program Studi PGMI, 2025)
This study examines the role of Islamic work culture in enhancing teacher motivation and performance at SD IT Nurul Hikmah, Tanjung Jabung Timur. Through qualitative methods, the research highlights three primary strategies: fostering Islamic work culture, implementing supervision grounded in Islamic values, and applying Hackman and Oldham’s Job Characteristic Model. The integration of Islamic principles such as integrity, accountability, and sincerity into daily school operations has proven effective in creating a harmonious and productive work environment. Key findings demonstrate that dimensions of the Job Characteristic Model—Task Significance, Skill Variety, and Feedback—significantly contribute to teacher motivation and professional growth. This approach not only supports the achievement of educational goals but also shapes teachers into highly spiritual and professional individuals.